Emergency law : rights, liabilities and duties of emergency workers and volunteers - Eburn, Michael (Leichhardt, N.S.W. : Federation Press, 2010)
This invaluable handbook is a must for any person who may be called upon to assist in an emergency, whether as a member of an emergency service organisation, or as part of their work duties (as medical or nursing practitioners, company first aid or fire safety officers), or as a volunteer. It outlines legal rights and obligations.
Foreword by Professor John Handmer -- Ch 1. Legal principles -- Ch 2. First aid / prehospital care -- Ch 3. Fire-fighting and rescue -- Ch 4. Ambulance, fire and emergency services -- Ch 5. Disaster planning and response -- Ch 6. Liability of emergency services -- Ch 7. Driving emergency vehicles -- Ch 8. Compensation for rescuers -- Ch 9. Conclusion -- Appendix 1. Ready Reference: Powers of Emergency Officers.
Previous ed.: 2005.
Includes index.
Includes bibliographical references and index.
Keywords: Volunteers -- Legal status, laws, etc -- Australia; Emergency medical personnel -- Legal status, laws, etc -- Australia; Fire fighters -- Legal status, laws, etc -- Australia